New species and new records of Manota Williston (Diptera, Mycetophilidae) from Thailand, with a key to the Oriental and Palaearctic species - Hippa, Heikki (Zootaxa, 2011)
The following new species are described: Manota aquila, M. falcata, M. flammula and M. subcollina. The following are reported as new species for the Thailand fauna: M. calcarata Hippa, M. clausa Hippa, M. curvata Hippa, M. duplex Hippa, M. fera Hippa, M. ferrata Hippa, M. horrida Hippa, M. perangulata Hippa & Ševčík, M. pollex Hippa, and M. transversa Hippa. New records within Thailand are given of the following species: M. aconcinna Hippa, M. acutangula Hippa, M. ancylochaeta Hippa, M. biunculata Hippa, M. dentata Hippa & Papp, M. epigrata Hippa, M. globigera Hippa, M. heptacantha Hippa, M. inflata Hippa, M. mirifica Hippa & Papp, M. oligochaeta Hippa, M. ovata Hippa, M. pectinata Hippa, M. pellii Hippa, M. perlobata Hippa, M. perpusilla Hippa, M. planilobata Hippa, M. plusiochaeta Hippa, M. roslii Hippa, M. simplex Hippa, M. subferrata Hippa, M. submirifica Hippa, M. tetrachaeta Hippa, M. ulu Hippa, and M. vesicaria Hippa. Male genitalia of M. aconcinna Hippa are redescribed. The number of the known Oriental species of Manota is now 84, of which 56 are recorded from Thailand. A key to the Oriental and Palaearctic species is given.